Fixed Capital Formation in the British Economy, 1956-1965 - J.C.R. Rowley (Queen's University, Department of Economics, 1969)
Few econometric analyses dealing with aspects of the British post-war economy were available. In 1968, a study sponsored by the Brookings Institution was compelled to acknowledge the absence of any econometric investigation of the British system of investment incentives. In the following sections of this paper, this omission is remedied, and some empirical reults are tabulated for a group of models applied to data derived for one decade of the post-war British economy.
Keywords: 330